"The Effect Of The Hawley Type Of Retaıner On The Upper And Lower Incısor Posıtıons In Extractıon Cases" - Oktay Üner; Müfide Dinçer (Galenos Yayinevi, 1988)
In this longitudinal study, the effect of the Hawley retainer on the stability of upper and lower incisor positions was investigated during the retention period following active orthodontic treatment, 10 patients, mean skeletal aged 14 years 3 months, who have Angle Class I malocclusion were examined. Patients were treated after the extraction of four first premolars by using "Modified Edgewise" Technique. Orthodontic treatments were performed at a mean period of 20.7 months. The Hawley retainers were used during the retention period for 19 months after the active orthodontic treatment The cephalometric radiographs of all patients were taken at the beginning and at the end of treatment and retention. On the tracing of cephalometric radiographs nine angular and seven linear measurements were made. The mean values of these measurements were calculated and statistically evaluated. The results of this study indicate that the Hawley type of retainers caused to lingoversion of mandibular incisors, increase of inter-incisal angles and retrusion of lower lip.